Additive manufacturing of silicon nitride ceramics: A review of advances and perspectives. Issue 6 (15th August 2022) - Dong, Xingjie; Wu, Jianqin; Yu, Honglin; Zhou, Qing; Wang, Wenqing; Zhang, Xueqin; Zhang, Lu; Li, Ling; He, Rujie
Abstract: Silicon nitride (Si3 N4 ) ceramic has been widely applied in various engineering fields. The emergence of additive manufacturing (AM) technologies provides an innovative approach for the fabrication of complex‐shaped Si3 N4 ceramic components. This article systematically reviews the advances of the AM of Si3 N4 ceramic in recent years and forecasts the potential perspectives in this field. This review aims to motivate future research and development for the AM of Si3 N4 ceramic.